2016
DOI: 10.1155/2016/2816056
|View full text |Cite
|
Sign up to set email alerts
|

Daphnetin Protects against Cerebral Ischemia/Reperfusion Injury in Mice via Inhibition of TLR4/NF-κB Signaling Pathway

Abstract: Growing evidences indicate that immune-mediated mechanisms contribute to the development of cerebral ischemia/reperfusion (I/R) injury. Daphnetin (DAP) is a coumarin derivative extracted from Daphne odora var., which displays anti-inflammatory properties. However, the effect of DAP on cerebral I/R injury is not yet clear. Recent studies have demonstrated that TLR4/NF-κB signaling pathway takes part in the damaging inflammatory process of cerebral I/R injury. The present study aimed to investigate the effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(39 citation statements)
references
References 25 publications
(38 reference statements)
0
39
0
Order By: Relevance
“…Ischaemic stroke (IS), which accounts for approximately 85% of all strokes is caused by immediate deprivation of both glucose and oxygen caused by the rapid loss in blood flow to brain [1,2]. Accumulating evidence revealed that IS becomes one of the leading cause of mortality and disability in adults all through the world [3]. Nowadays, the therapies for IS are intravenous alteplase administered within 4.5 h after symptom onset and mechanical thrombectomy [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Ischaemic stroke (IS), which accounts for approximately 85% of all strokes is caused by immediate deprivation of both glucose and oxygen caused by the rapid loss in blood flow to brain [1,2]. Accumulating evidence revealed that IS becomes one of the leading cause of mortality and disability in adults all through the world [3]. Nowadays, the therapies for IS are intravenous alteplase administered within 4.5 h after symptom onset and mechanical thrombectomy [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the TLR4/NF-κB signaling pathway accelerates the inflammatory process in neuroinflammatory injury [39][40][41]. NF-κB is a nuclear transcription factor that regulates the expression of numerous genes that are responsible for regulating apoptosis, tumorigenesis, inflammation, and various autoimmune diseases [42].…”
Section: Discussionmentioning
confidence: 99%
“…Daphnetin is a natural coumarin derivative isolated from the traditional Chinese medicine genus Daphne , which is traditionally used for the treatment of rheumatoid arthritis . Daphnetin has been shown to possess broad bioactivities such as antioxidative, anti‐inflammatory, antitumor, and antiarthritis effects . However, the role of daphnetin in osteoclast formation remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Daphnetin has been shown to possess broad bioactivities such as antioxidative, anti-inflammatory, antitumor, and antiarthritis effects. [9][10][11][12][13] However, the role of daphnetin in osteoclast formation remains unclear. In this study, we investigated the effects of daphnetin on RANKL-induced osteoclastogenesis using bone marrow-derived macrophages (BMMs).…”
Section: Introductionmentioning
confidence: 99%